Optimal Printing and Post-Processing Modes of Polymer Products Manufactured Using SLA-Technology of Additive Мanufacturing - T. A. Pratasenia; A. P. Kren (Приборы и методы измерений, 2023)
Innovative production technologies, such as additive synthesis, is inextricably linked with the development of methods for assessing the quality of manufactured products. At the initial stage of introducing of new production methods into various industries, the most studied and widely used control methods are usually used. In most cases these are standard destructive tests. As an alternative to standard tensile tests used to evaluate the elastic and strength properties of polymer products produced using SLA-technology, the dynamic indentation method is studed in this work. Using the samples of the high-temperature photopolymer resin High Temp RS-F2-HTAM-01, the possibility of optimizing 3D printing methods and post-processing modes based on dynamic indentation data is shown. It has been shown that non-pigmented photopolymers are most susceptible to embrittlement due to their ability to transmit UV radiation into the volume of the synthesized material. It was found that the embrittlement of a polymer material has a lesser effect on the result of measuring its dynamic hardness than on its tensile strength. It has been established that post-curing of polymer products at high temperatures (up to 160 °C) and UV radiation with a power of 39 W can increase their strength and elastic modulus by 170 % and 85 %, respectively, compared to the state before treatment. It has been proven that the sensitivity of the dynamic indentation method to changes in the physical and mechanical characteristics of products obtained using SLA-technology under various types and modes of their post-processing is comparable to the sensitivity of standard tensile tests.